Effects of reduced-risk pesticides and plant growth regulators on rove beetle (Coleoptera: Staphylinidae) adults - Echegaray, Erik R.; Cloyd, Raymond A. (My University, 2013)
In many regions, pest management of greenhouse crops relies on the use of biological control agents; however, pesticides are also widely used, especially when dealing with multiple arthropod pests and attempting to maintain high esthetic standards. As such, there is interest in using biological control agents in conjunction with chemical control. However, the prospects of combining natural enemies and pesticides are not well known in many systems. The rove beetle, Atheta coriaria (Kraatz), is a biological control agent mainly used against fungus gnats (Bradysia spp.). This study evaluated the effects of reduced-risk pesticides and plant growth regulators on A. coriaria adult survival, development, and prey consumption under laboratory conditions. Rove beetle survival was consistently higher when adults were released 24 h after rather than before applying pesticides. The pesticides acetamiprid, lambda-cyhalothrin, and cyfluthrin were harmful to rove beetle adults, whereas Beauveria bassiana (Balsamo) Vuillemin, azadirachtin, and organic oils (cinnamon oils, rosemary oil, thyme oil, and clove oil) were nontoxic to A. coriaria adults. Similarly, the plant growth regulators acymidol, paclobutrazol, and uniconazole were not harmful to rove beetle adults. In addition, B. bassiana, azadirachtin, kinoprene, organic oils, and the plant growth regulators did not negatively affect A. coriaria development. However, B. bassiana did negatively affect adult prey consumption. This study demonstrated that A. coriaria may not be used when applying the pesticides, acetamiprid, lambda-cyhalothrin, and cyfluthrin, whereas organic oils, B. bassiana, azadirachtin, and the plant growth regulators evaluated may be used in conjunction with A. coriaria adults. As such, these compounds may be used in combination with A. coriaria in greenhouse production systems.
Citation: Echegaray, Erik R., and Raymond A. Cloyd. 2012. “Effects of Reduced-Risk Pesticides and Plant Growth Regulators on Rove Beetle (Coleoptera: Staphylinidae) Adults.” Journal of Economic Entomology 105 (6): 2097–2106. https://doi.org/10.1603/EC12244.
Keywords: Insecticide; Botanical; IGRs; Beauveria bassiana; Survival